The discourse of the US alt-right online - a case study of the Traditionalist Worker Party blog - Lorenzo-Dus, Nuria; Nouri, Lella (Critical discourse studies, 2021)
The use of social media by extreme right groups and the self-proclaimed formation of the 'alt-right' in recent years have been linked to the rise in US white nationalism. Against a backdrop of widespread concern regarding the growing nature of the 'alt-right' phenomenon, this article responds to the pressing need to understand its appeal. Specifically, we examine the discursive means by which a hitherto unexamined US 'alt-right' group, the Traditionalist Worker Party, constructs its group identity and ideology online. Corpus assisted discourse analysis of this group's blog (c. one million words) reveals that the Traditionalist Worker Party regularly mobilises five discourses (groupness, party politics, race, religion/tradition, change) in order to assert subject positions of victimhood for its (to be) members, alongside recurrent use of explicit out-grouping strategies. The out-groups are blamed for a general malaise - an uncertain, chaotic reality that can and must be changed through affiliation with the Traditionalist Worker Party. The study also shows that the Traditionalist Worker Party constructs itself a highly entitative group as a means to enhancing its recruitment appeal.